Effect of Financial Literacy, Financial Reporting, And Risk Management on Financial Performance of Msmes With Innovative Behavior As Mediator - Sudharmasto, Septianto; Hastuti, Theresia Dwi (E-Jurnal Akuntansi; Vol 35 No 3 (2025), 2025)
The purpose of this study is to determine the influence of financial literacy, financial report preparation ability and risk management on financial performance. Types of quantitative research. The sample method used is nonprobability sampling with the Convenience sampling technique of 280 MSME respondents in Central Java. Financial literacy has been proven to have a positive effect on the financial performance of MSMEs. The ability to prepare financial statements has been proven to have a positive effect on the financial performance of MSMEs. Innovative behavior is able to mediate the relationship between financial literacy, and financial performance. Innovative behavior can mediate the relationship between the ability to prepare financial statements and financial performance. Keywords: Financial Literacy; Financial Report; Financial Performance; Risk Management